ANALISIS PERAN PEMERINTAH DAERAH DALAM PENCEGAHAN PENYEBARAN COVID-19 DI WILAYAH PERBATASAN - Fandi Hi. Latief; Sri Ka’bah (Pusat Riset dan Publikasi, 2023)
This study aims to observe and describe the role of local governments in preventing the spread of Covid-19 in the Border Region. This research was conducted in South Morotai Sub District, Morotai Island District. The type of this research is a qualitative with a qualitative approach. The type of data used in this study is qualitative data on research informants' answers regarding research problems obtained directly from research informants through interviews. The informants in this study consisted of the Head of the Morotai Island District Health Office, the Head of the district vaccination team, the District Vaccination Team, and the Head of the South Morotai Sub District Health Center. The stages of data analysis in this study used qualitative data analysis, including data collection, data presentation, data reduction and conclusion/verification. The results of this study indicate that the local government has carried out two roles in preventing the spread of Covid-19 in the South Morotai District, Morotai Island Regency, namely the role of regulation and services. The role of regulation is carried out by establishing anticipatory policies, including maximizing level 3 mobility restrictions followed by 7 (seven) actions/roles by Government of the Morotai District. Meanwhile, the role of services is carried out by implementing a vaccination program for all elements in South Morotai District, Morotai Island Regency, starting from government apparatus, TNI, POLRI, ASN to the general public.